Novel, cross-restricted, conserved, and immunodominant cytotoxic T lymphocyte epitopes in slow progressors in HIV type 1 infection. - Goulder, P; Bunce, M; Krausa, P; McIntyre, K; Crowley, S; Morgan, B; Edwards, A; Giangrande, P; Phillips, R; McMichael, A (1996)
HIV-specific cytotoxic T lymphocytes (CTLs) play an important role in the immune response to HIV infection. Long-term nonprogressors (LTNPs) or slow progressors (SPs) in HIV infection may make qualitatively different CTL responses compared to those generated by seropositive individuals who progress to disease at a faster rate. The class I molecule HLA-B*57 has been identified as one restriction element overrepresented in SP groups studied, and, together with the closely related molecule HLA-B*58, occurs commonly in ethnic groups where HIV is most prevalent. In this study, we have identified five new HLA-B*57-restricted CTL epitopes recognized by SP donors, one of which is also HLA-B*5801 restricted. These HLA-B*57-restricted responses represent the dominant HIV-specific CTL response in each of the SP donors tested. These and other such epitopes may be an important component in future vaccine design.